PRODUKSI AMONIA, UNDEGRADED PROTEIN DAN PROTEIN TOTAL SECARA in vitro BUNGKIL BIJI KAPUK YANG DIPROTEKSI DENGAN TANIN ALAMI - Jenny, Imelda; Surono, Surono; Christiyanto, Marry (Animal Agriculture Journal, 2012)
Ransum protein needs are influenced by the amount required for basic living,growth, and production. Cotton seed oilcake potential as a protein supplement foranimal feed because protein that present in cotton seed oilcake reaches 29.57 to31.13%. Cotton seed oilcake containing high protein and good quality given toruminants largely degraded by microbes in the rumen, so that influence to theefficiency of protein utilization. Protein is one of the important nutrients needed byruminants at various levels of production and the various phases of his life. A highprotein in feed ingredients needs to be done protection that are not easily degradedby rumen microbes Protection of proteins can be done in several ways, namelyphysical, chemical and biological. The study aims to assess fermentability feedingredients protein source that is protected by tannins from extracts of tea waste interms of measuring the concentration of NH3, Undegraded Protein and total proteinproduction. The results showed that the concentration of ammonia in cotton seedoilcake protected with increased of tannin levels decrease NH3 concentration andincrease the levels of UDP (p <0.05) and increase total protein. The average of NH3concentration, UDP and total protein in T0, T1, T2, T3 consecutive are (7,52 mM;10,91%; 369,62 mg/g), (6,60 mM; 11,45%; 439,50mg/g), (6,55 mM; 12,41%;457,35 mg/g), (6,32 mM; 13,44%; 514,95 mg/g). The conclusions of this study thatthe cotton seed oilcake protected dregs of tea tannin extracts with level 0,25%,0,50% and 0,75% can decrease the concentration of NH3, increase UDP and totalprotein. The protection level of Cotton seed oilcake with tannin extract the best teawaste is level 0,75% (% b/b BK).